The Marlborough Mound : Prehistoric Mound, Medieval Castle, Georgian Garden - Barber, Richard (Boydell & Brewer, Incorporated, 2022)
The Marlborough Mound has recently been recognised as one of the most important monuments in the group around Stonehenge. It was also a medieval castle and a feature in a major 17th century garden. This is the first comprehensive history of this extraordinary site.